2017
DOI: 10.1002/marc.201700212
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and Architectural Control in Glycopolymer Synthesis

Abstract: Glycopolymers are synthetic-carbohydrate-containing materials capable of interacting and binding to specific targeting lectins, which are crucially important in many biologically active processes. Over the last decade, advances in synthetic chemistry and polymerization techniques have enabled the development of sequence and architecturally controlled glycopolymers for different types of bioapplications, such as drug delivery and release purposes, gene therapy, lectin-based biosensors, and much more in the futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 118 publications
0
56
0
Order By: Relevance
“…In particular, specific sugar moieties can be positioned at the surface of the particles, to target a class of protein receptors known as lectins. Previous research into using sugar‐lectin targeting for drug delivery has shown that presenting the targeting sugar in a high concentration, such as that on the surface of a particle, increases the targeting efficiency of a drug delivery vector, taking advantage of the “glycocluster effect.” Recent developments in this area have applied the principle of targeting lectins with glycopolymers in more refined systems, using sequenced defined polymers alone and in combination with stimuli responsive polymers to elicit a more specific biological targeting . Among the many stimuli responsive systems reported, poly( N ‐isopropylacrylamide) is commonly used for temperature response, where heating above the cloud point of the system triggers a self‐assembly or reveals a glycopolymer .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, specific sugar moieties can be positioned at the surface of the particles, to target a class of protein receptors known as lectins. Previous research into using sugar‐lectin targeting for drug delivery has shown that presenting the targeting sugar in a high concentration, such as that on the surface of a particle, increases the targeting efficiency of a drug delivery vector, taking advantage of the “glycocluster effect.” Recent developments in this area have applied the principle of targeting lectins with glycopolymers in more refined systems, using sequenced defined polymers alone and in combination with stimuli responsive polymers to elicit a more specific biological targeting . Among the many stimuli responsive systems reported, poly( N ‐isopropylacrylamide) is commonly used for temperature response, where heating above the cloud point of the system triggers a self‐assembly or reveals a glycopolymer .…”
Section: Introductionmentioning
confidence: 99%
“…Recently developed precise control synthesis approaches allow to design new polymeric architectures in high precision with improved binding affinity due to their enhanced glycocluster effect. [ 3 ] These studies are very important to understand and modulate the involvement of lectin–glycopolymer interaction in terms of different biological and medical functions. In particular, the calcium‐dependent carbohydrate‐binding lectins (C‐type lectins) on immune cells providing very high carbohydrate binding affinity can recognize different types of pathogens and viruses selectively by their cognate carbohydrate ligands to isolate infectious events, and trigger adaptive immunity.…”
mentioning
confidence: 99%
“…[1] As the term "counterreceptor" implies,tissue lectins often have as mall set of binding partners that they select from the broad panel of natural glycoconjugates. Fittingly,t he testing of bioinspired glycoclusters,g lycodendrimers,a nd glycopolymers [3] have already provided valuable insights into the enormous potential of the mode of glycan presentation to regulate lectin avidity. Fittingly,t he testing of bioinspired glycoclusters,g lycodendrimers,a nd glycopolymers [3] have already provided valuable insights into the enormous potential of the mode of glycan presentation to regulate lectin avidity.…”
mentioning
confidence: 99%
“…Aggregation of GDSs (Lac = 0.2 mm,900 mL) self-assembled from 3-Lac Gal-1 (A), its GG-linked homodimer (Gal-1) 2 -GG (B), trimer (Gal-1)3 -GG (C), and tetramer (Gal-1)4 -GG (D) tested at concentrations from 0.125 mg mL À1 to 1mgmL À1 in PBS (pH 7.4).…”
mentioning
confidence: 99%
See 1 more Smart Citation